Increased vitamin B6 turnover is associated with greater mortality risk in the general US population: a prospective biomarker study - Schorgg, Paula; Karavasiloglou, Nena; Beyer, Anika; Cantwell, Marie; Danquah, Ina; Gojda, Jan; Rohrmann, Sabine; Cassidy, Aedin; Bärnighausen, Till; Cahova, Monika; Kühn, Tilman (Clinical nutrition, 2022)
Background & aims - Vitamin B6 status and mortality risk are inversely associated in different patient groups, while prospective studies in the general population are lacking. Here, for the first time, we evaluated the association between biomarkers of vitamin B6 status and mortality risk in a large population-based study. - Methods - The vitamin B6 vitamers pyridoxal-5′-phosphat (PLP) and 4-pyridoxic acid (4-PA) were measured by high-performance liquid chromatography in the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2010. Participants' vital status and causes of death were recorded until December 2015. Multivariable Cox regression analyses were carried out to estimate Hazard Ratios (HRs) and 95% confidence intervals (CIs) of mortality across quintiles of PLP, 4-PA, and the ratio of 4-PA and PLP. - Results - Out of 15,304 study participants aged between 20 and 85 years at baseline, 1666 (7.7%) died during a median follow-up time of 7.8 years. An inverse association between PLP and mortality was found in a multivariable model adjusted for socioeconomic and lifestyle factors but became statistically non-significant upon adjustment for routine biomarkers (C-reactive protein, creatinine, albumin, and alkaline phosphatase). There was a significant linear trend for a positive association between 4-PA levels and mortality risk in the fully adjusted regression model, although a comparison of extreme quintiles (quintile 5 vs. quintile 1) did not show a significant difference (HRQ5vs.Q1 (95% CI): 1.19 (0.93, 1.51), plinear trend = 0.02). A positive association between the 4-PA/PLP ratio and all-cause mortality was observed in the multivariable model, with an HRsQ5vs.Q1 of 1.45 (95% CI: 1.14, 1.85; plinear trend<0.0001). There were no significant associations between the biomarkers and cardiovascular or cancer mortality. The association between 4-PA/PLP and mortality risk was heterogeneous across age groups, and only statistically significant among participants older than 65 years at baseline (HRQ5vs.Q1 (95% CI): 1.72 (1.29, 2.29), plinear trend<0.0001). In this group, 4-PA/PLP was also associated with cancer mortality, with an HR Q5vs.Q1 of 2.16 (1.20, 3.90), plinear trend = 0.02). - Conclusion - Increased vitamin B6 turnover, as indicated by a higher 4-PA/PLP ratio, was associated with all-cause and cancer mortality among the older U.S. general population. Intervention trials are needed to assess whether older individuals with a high 4-PA/PLP ratio would benefit from increased vitamin B6 intake.
Gesehen am 26.08.2022